The sharing economy: understanding the affordances and barriers that influence the assimilation of digital platforms for handy services in South Africa - Malatjie, Phaswana (Department of Information Systems, 2025)
The need to further Information Systems is essential. Innovations in technology have led to rapid developments and as technology continues to advance, so is the need to understand the changes from Information Systems' view. Several studies have explored the sharing economy services such as automotive, house-sharing, and handy services. The studies predict that sharing economy services will add billions of dollars to the global economy due to its exponential growth over the last decade. Challenges such as unemployment are impacted by the growth of this innovation in countries like South Africa. Consequently, the primary objective of this study is to understand the affordances and barriers that influence the assimilation of digital platforms for handy services. This could aid in highlighting potential solutions that could aid in reducing the high unemployment rate that we have in South Africa. By conducting a literature review, the researcher understood the benefits and challenges found in other areas of sharing economy services in South Africa. Furthermore, the literature revealed gaps around the sharing economy services relating to load-shedding, regulations, social exclusion and potential future directions for some of the issues. This study could not find an appropriate theoretical framework for understanding how barriers influence the affordances in the context of digital platforms for handy services. For this reason, the research sets out to investigate the affordances and barriers that assimilate the use of sharing platforms for handy services. This study adopted a qualitative approach to answer the research questions. Data was collected by conducting semi-structured interviews with users and potential users of sharing platform for handy services. The data was analysed using inductive thematic analysis method to construct the major themes. Two sampling techniques (heterogeneous and snowballing) were used and a group of twenty-two participants who provided diverse views that aided in answering the research question were interviewed. The research object was addressed by constructing a two causal loops diagrams and a conceptual model, which explained how the affordances and barriers influence the assimilation of sharing platforms for handy services. The research findings reveal a gap in marketing strategies that can facilitate the inclusion of lower-income groups. Furthermore, this research findings highlighted gaps around security measures required to ensure users' safety and regulations to ensure that all South Africans' can enjoy the use of sharing platforms for handy services. Lastly, the research revealed the opportunities such as sharing platforms for handy services exploring partnerships with technical training institutions and/or government agencies to help identify more skilled job seekers and contribute to economic development goals. Furthermore, this could aid in reducing unemployment in South Africa.